A Matter of Principle - Marshall Anderson (Association of American Medical Colleges, 2007)
Abstract This problem-based learning (PBL) case is suitable for first- or second-year medical students in a biochemistry and molecular biology course as either a paper-based or standardized patient scenario. The case consists of two National Guard soldiers going on a hunger strike, one by taking electrolytes and the other by drinking fruit juices. The patients are followed for a little over 7 weeks. The patient taking electrolytes develops symptoms of marasmus while the patient drinking fruit juice develops symptoms of Kwashiorkor. Students typically initially assume that patients with marasmus would have more severe problems than a corresponding patient with Kwashiorkor. However, by the end of the case they learn that protein malnutrition can often have a poorer outcome than marasmus. The case ties together many basic concepts of biochemistry, nutrition, and interorgan metabolic relationships. It utilizes progressive discovery as students are supposed to identify unfamiliar items and concepts and both research and discuss them with their PBL group. This case has been modified for use at Sackler Medical School in Tel Aviv by Sheryl Shoham, MD.